Cost of living and standard of living nexus: the determinants of cost of living - Rusli Latimaha; Ismal, N.A.; Bahari, Z. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cost of living and standard of living are two elements that have strong causal relationship. Determining which one causes the other would give some ideas to policy makers about mitigating the adverse impact of the rising cost of living. This study investigates whether the standard of living causes the cost of living. It further identifies the factors influencing the cost of living. Based on Malaysian data over 1980-2014, we use Toda Yamamoto causality model, to identify whether the cost of living Granger causes the standard of living or vice-versa. In identifying the factors that influence the cost of living, we use, the Autoregresive Distributed Lag (ARDL) Bounds test. The result indicates that there is evidence of unidirectional Granger causality between the cost of living and the standard of living. It addition, we found that the cost of living can be used to better predict the standard of living by considering the lagged values of the cost of living rather than the lagged values of the standard of living. The results further show that there is a long-run relationship between the cost of living and the factors of gross domestic product per capita, population growth, unemployment rate and degree of openness. PRO © 2020 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.